From Conventional to Smart Prosthetics: Redefining Complete Denture Therapy Through Technology and Regenerative Science - Andrea Bors; Simona Mucenic; Adriana Monea; Alina Ormenisan; Gabriela Beresescu (Medicina)
Background and Objectives: Complete dentures remain a primary solution for oral rehabilitation in aging and medically compromised populations. The integration of digital workflows, regenerative materials, and smart technologies is propelling prosthodontics towards a new era, transcending the limitations of traditional static prostheses. Materials and Methods: This narrative review synthesizes historical developments, current practices, and future innovations in complete denture therapy. A comprehensive review of literature from PubMed, Scopus, and Web of Science (2000–2025) was conducted, with a focus on materials science, digital design, patient-centered care, artificial intelligence (AI), and sustainable fabrication. Results: Innovations in the field include high-performance polymers, CAD–CAM systems, digital impressions, smart sensors, and bioactive liners. Recent trends in the field include the development of self-monitoring prostheses, artificial intelligence (AI)-driven design platforms, and bioprinted regenerative bases. These advances have been shown to enhance customization, durability, hygiene, and patient satisfaction. However, challenges persist in terms of accessibility, clinician training, regulatory validation, and ethical integration of digital data. Conclusions: The field of complete denture therapy is undergoing a transition toward a new paradigm of prosthetics that are personalized, intelligent, and sustainable. To ensure the integration of these technologies into standard care, ongoing interdisciplinary research, clinical validation, and equitable implementation are imperative.